Christian fundamentalism in America a cultural history - New, David S. (McFarland & Co. Publishers, 2012)
"This book examines the history of conservative American Christianity as it interacts with liberal beliefs. With the Enlightenment, the Puritan sense of mission faded, but was rekindled with the Great Awakening. It is history with a human touch, emphasizing personalities from Jonathan Edwards and William Jennings Bryan to David Koresh and Jim Jones"--Provided by publisher.